Cashew Apples in Ghana: Stakeholders’ Knowledge, Perception, and Utilization - Yaw Gyau Akyereko; Faustina Dufie Wireko-Manu; Francis Alemawor; Mary Adzanyo (International Journal of Food Science)
Cashew (Anacardium occidentale), a crop projecting Ghana internationally beside cocoa, is usually cultivated for its nut, for both local and international markets. The cashew apple is underutilized in many African countries. This study is aimed at determining the knowledge, perception, and utilization of cashew apples in Ghana among stakeholders in the cashew value chain. Results from the study showed that the cashew industry consisted of farmers (89.1%), nut buyers (6.8%), extension officers (3.5%), and processors (0.6%) with uneven distribution of males (66.2%) and females (33.8%). Cashew apple utilization was low (<10%), though 84.37% had in-depth knowledge on the health benefits and value-added products made from the apples. Cashew apple is mainly utilized as fresh fruits or juice, with minor uses as an ingredient in food preparation, animal feed formulation, and production of mushroom, weedicide, ethanol, and manure. The cashew apple processors identified high cost of processing equipment, perishability of apples, lack of capital, market, technical know-how, and government support as challenges. Based on these findings, education of the stakeholders on value addition or processing of the apples at household and industrial levels and provision of stimulus packages to private processors are recommended to maximize cashew apple utilization in Ghana.